1996
DOI: 10.1007/bf02044113
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the adrenocortical response during septic shock and after complete recovery

Abstract: Adrenocortical response to corticotropin is attenuated in patients with septic shock and high-output circulatory failure compared to the response in the much less stressful condition after recovery. The attenuated adrenocortical responsiveness may be explained by effects of circulating mediators from the systemic inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(45 citation statements)
references
References 23 publications
3
36
1
5
Order By: Relevance
“…This prevalence of relative adrenal insufficiency is among the highest previously reported in septic shock. [11][12][13][14][15][16][17][18] Our data also confirm that in the setting of a septic shock, diagnosing adrenal insufficiency based on clinical data is very difficult. Only the presence of severe hepatic failure (Child-Pugh grade C) was an indicator of adrenal dysfunction in our patients.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This prevalence of relative adrenal insufficiency is among the highest previously reported in septic shock. [11][12][13][14][15][16][17][18] Our data also confirm that in the setting of a septic shock, diagnosing adrenal insufficiency based on clinical data is very difficult. Only the presence of severe hepatic failure (Child-Pugh grade C) was an indicator of adrenal dysfunction in our patients.…”
Section: Discussionsupporting
confidence: 72%
“…[11][12][13][14][15][16][17][18] Although plasma cortisol levels in these patients are normal or increased, they are inappropriately low to control the inflammatory response. Diagnosis of relative adrenal insufficiency is not possible on clinical grounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Este término se ha utilizado con frecuencia, los últimos años, en Medicina Intensiva para referirse a la necesidad de suplementación de cortisol y los beneficios que significan 37 . En los pacientes críticos, la falta de reconocimiento de esta entidad, o su reconocimiento tardío, se asocia a mayor incidencia de shock resistente a terapia con fluidos y vasopresores y mayor mortalidad [38][39][40][41] . El diagnóstico de este trastorno suprarrenal funcional no es posible a partir de parámetros clínicos 42 y actualmente se basa en la determinación sérica del cortisol total.…”
Section: Insuficiencia Suprarrenal Relativaunclassified
“…Therefore, perhaps the use of repetitive measurements of plasma cortisol over time together with repetitive ACTH stimulation tests could shed more light on the nature of adrenocortical dysfunction in critically ill patients. It has already been suggested that the cortisol responsiveness to ACTH restores after recovery of illness, while a decreasing cortisol response during repetitive ACTH-testing was associated with a poor prognosis (23,49,50). Unfortunately, large enough and well-designed prospective clinical studies of systematic ACTH stimulation tests The use of repetitive cortisol measurements may be additionally important, taking into account the limitations of a single total or free cortisol measurement.…”
Section: E Boonen and G Van Den Berghementioning
confidence: 99%